2017
DOI: 10.1556/066.2017.46.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing sushi meal as representative of non-traditional meal: Consumption among Czech consumers

Abstract: Determination of consumers' acceptance level of sushi meal among Czech respondents was the main aim. The survey included 1352 respondents that fi lled in a questionnaire on their demographic characteristics and food preferences regarding their acceptance of sushi meal. Additionally, 79 volunteers participated in sorting sushi among other 14 popular meals in the Czech Republic, according to their assumed situations. The results indicate that sushi is highly accepted among Czech consumers (more than 80% of respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Furthermore, easy to prepare, time saving and minimum physical effort for preparation and clean up were the key factors which positively influenced purchase intention and consumption of convenience food [3]. Previous studies carried out under a wide range of social, cultural and economic conditions support the findings of the present study [5,9,31,64,73]. Olsen et al [2] revealed that convenience orientation was the most important factor influencing convenience food consumption in Poland and Spain.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, easy to prepare, time saving and minimum physical effort for preparation and clean up were the key factors which positively influenced purchase intention and consumption of convenience food [3]. Previous studies carried out under a wide range of social, cultural and economic conditions support the findings of the present study [5,9,31,64,73]. Olsen et al [2] revealed that convenience orientation was the most important factor influencing convenience food consumption in Poland and Spain.…”
Section: Discussionsupporting
confidence: 79%
“…The confluence of these driving vectors leads to a forthcoming sprawl of convenience food [3,28,29]. Several studies in the recent past have been carried out to seek the effect of various factors on convenience food choice, most of which focused on markets in developed and industrialised countries [8,10,[12][13][14][15][16]22,26,30,31]. Due to diversity in tradition, culture, food habits, social structure, religious belief and ethical values, the consumers in emerging economies such as India, might not respond to such factors in the same way as reported in the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ðordević and Buchtova [98], the rarity of a product can be seen as a potential opportunity, which affects its acceptance and the frequency of consumption of the product. Undoubtedly, organic products, due to their price, for some segments of consumers, meet this condition, especially in relation to goat milk products and its derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature it has been discussed that health, mood, convenience, price, familiarity, social norms, natural and ethical concerns, and taste are prime issues considered by consumers when making food choices [ 6 , 7 , 8 , 9 , 10 ]. Eertmans et al (2006) conducted a survey using the food choice questionnaire (FCQ) in different countries and found that in Italy, health and nature content, convenience and mood were the most important issues Italian consumer concerned in making their food choices [ 11 ].…”
Section: Introductionmentioning
confidence: 99%